Cerebrospinal Fluid - Kuru Bektaşoğlu, Pınar; Gürer, Bora (IntechOpen, 2022)
Cerebrospinal fluid is an essential, clear, and colorless liquid essential for maintaining homeostasis of the brain and neuronal functioning. Its secretion in adults ranges from 400 to 600 ml per day and it is renewed about four or five times daily. Cerebrospinal fluid is mainly reabsorbed from arachnoid granulations. Any disruption in this well-regulated system, such as overproduction, decreased absorption, or obstruction, could lead to hydrocephalus. This book contains essential knowledge about cerebrospinal fluid anatomy and physiology, pathologies related to cerebrospinal fluid, and treatment strategies for cerebrospinal fluid disorders.